Nucleonic Direct Urca Processes and Cooling of the Massive Neutron Star by Antikaon Condensations - Yan Xu; Wen Bo Ding; Cheng Zhi Liu; J. L. Han (Advances in Astronomy)
Nucleonic direct Urca processes and cooling of the massive neutron stars are studied by considering antikaon condensations. Calculations are performed in the relativistic mean field and isothermal interior approximations. Neutrino energy losses of the nucleonic direct Urca processes are reduced when the optical potential of antikaons changes from −80 to −130 MeV. If the center density of the massive neutron stars is a constant, the masses taper off with the optical potential of antikaons, and neutrino luminosities of the nucleonic direct Urca processes decrease for ρCN=0.5 fm−3 but first increase and then decrease for larger ρCN. Large optical potential of antikaons results in warming of the nonsuperfluid massive neutron stars. Massive neutron stars turn warmer with the protonic S01 superfluids. However, the decline of the critical temperatures of the protonic S01 superfluids for the large optical potential of antikaons can speed up the cooling of the massive neutron stars.